2021
DOI: 10.1136/jclinpath-2021-207742
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of mitotic activity in breast cancer: revisited in the digital pathology era

Abstract: The assessment of cell proliferation is a key morphological feature for diagnosing various pathological lesions and predicting their clinical behaviour. Visual assessment of mitotic figures in routine histological sections remains the gold-standard method to evaluate the proliferative activity and grading of cancer. Despite the apparent simplicity of such a well-established method, visual assessment of mitotic figures in breast cancer (BC) remains a challenging task with low concordance among pathologists whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 72 publications
0
23
0
Order By: Relevance
“…The analytical validity of Ki67 is also questionable due to the lack of consensus on scoring methods and cut-off values, the reliability of various antibodies, and the actual clinical utility [102][103][104]. Until now, the traditional visual morphological detection of mitotic figures using well-established methods in H&E sections remains the most widely used and accepted method in routine practice in most laboratories as it is an easy, rapid, and simple technique for assessment of growth rate and tumour behaviour [101,105,106].…”
Section: Assessment Of Ki67 In Bcmentioning
confidence: 99%
“…The analytical validity of Ki67 is also questionable due to the lack of consensus on scoring methods and cut-off values, the reliability of various antibodies, and the actual clinical utility [102][103][104]. Until now, the traditional visual morphological detection of mitotic figures using well-established methods in H&E sections remains the most widely used and accepted method in routine practice in most laboratories as it is an easy, rapid, and simple technique for assessment of growth rate and tumour behaviour [101,105,106].…”
Section: Assessment Of Ki67 In Bcmentioning
confidence: 99%
“…Studies using mitotic activity evaluated by semi-quantitative methods showed low reproducibility for grading and poor correlation with prognosis [ 18 ]. However, studies in breast cancer suggest that mitotic counting can be improved by quantitative methods [ 22 ]. In our study, mitotic counting was performed using p-HH3 immunostaining to reduce subjectivity, although it has to be mentioned that p-HH3 staining cannot be compared directly to mitosis counting on H&E sections.…”
Section: Discussionmentioning
confidence: 99%
“…with the highest mitotic count) should be assessed. If the mitotic frequency score falls very close to a score cut point, one or more further groups of 10 HPFs should be assessed to establish the correct (highest) score. Fields chosen for scoring are selected during a random meander along the peripheral margin of the selected tumour area. Only fields with a representative tumour burden should be used. The low‐power scan of the tumour can be used to provide an assessment of the typical tumour‐to‐stromal ratio. Only definite mitotic figures (in any phase of the growth cycle) should be counted 16 . Hyperchromatic nuclei and/or apoptotic nuclei should not be scored. The mitosis score depends on the number of mitoses per 10 HPFs.…”
Section: Highlights Of the Invasive Breast Cancer Dataset With A Focu...mentioning
confidence: 99%